ENHANCING BRAND EXPERIENCE ALONG WITH EMOTIONAL ATTACHMENT TOWARDS TRUST AND BRAND LOYALTY - Elia Ardyan; Heny Kurnianingsih; Ginanjar Rahmawan; Utomo Wibisono; Winata Winata (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2016)
Research on Samsung’s smartphone consumers in Surakarta, have aimed to (1) Test the influence of brand experience on brand trust; (2) Test brand beliefs on brand loyalty; (3) Test on emotional attachment brand experience; (4) Test emotional attachment on brand trust; (5) Test brand experience on brand loyalty. The sample of this research was obtained from 100 respondents who have purchased a Samsung smartphone with the number of the purchase more than once. Methods of analysis used in this study are Structural Equation Modelling. The results of this research indicate that: (1) Brand experience influenced brand trust positively and significantly; (2) The trust against a brand loyalty affect brand positively and significantly; (3) Brand experience have positive and significant effect on emotional attachment; (4) Emotional attachment affects brand trust positively and significantly; (5) Brand trust have the influence of brand loyalty positively but not significant.